Finding a proper "Mate": Comparison of left ventricular assist devices using cerebral oximetry. Issue 6 (June 2021) - Montgomery, Morgan L; Stannard, Blaine; Dzedzik, Siarhei; Lin, Hung-Mo; Anyanwu, Anelechi; Levin, Matthew A; Trinh, Muoi
Introduction: Axial-flow and centrifugal-flow left ventricular assist devices (LVAD) have been utilized in the management of heart failure, but it remains unknown whether these devices differ in end-organ perfusion. Our goal was to evaluate the association between device type and regional cerebral oxygen saturation (rSO2 ), and determine if this confers any benefit in short-term postoperative outcomes. Methods: Adult patients who underwent primary LVAD implantation at our institution from 2014 to 2019 were retrospectively analyzed. Patients were stratified into axial-flow and centrifugal-flow groups. Intraoperative rSO2 readings were used to calculate the change in mean rSO2 from pre- to post-bypass. Multivariable modeling was performed to compare delta rSO2 between groups, and to analyze the association between LVAD type and postoperative outcomes. Results: There were 152 patients included, of which 76 had an axial-flow device and 76 had a centrifugal-flow device implanted. The rSO2 level increased from pre-bypass to post-bypass on average 3.5% (CI: 2.1 to 5.0) for the axial group compared to 0.1% (CI: −1.2 to 1.4) for the centrifugal group, which was a significant difference (β = −2.22, CI: −4.21 to −0.32, p  = 0.022). Axial devices approached significance for lower odds of postoperative complications (OR: 0.35, CI: 0.11 to 1.06, p  = 0.063), and were associated with significantly shorter ICU LOS (β = −0.36, CI: −0.60 to −0.11, p  = 0.004). Conclusion: Axial devices resulted in a greater increase in rSO2 than centrifugal pumps after separation from CPB. Further investigation is warranted to evaluate the effect of LVAD selection on long-term end-organ perfusion and subsequent patient outcomes.